(untitled) (ENTHYMEMA, 2020)
Taking up the Foucaultian notion of epistemes, the thesis we intend to defend is that between the eighties and nineties of the twentieth century there was an epistemic rupture in the West that also had an obvious impact on literature. This rupture can be measured in particular if we look at the paradigm around which the human and social sciences are reconfigured. If this paradigm from the end of the 19th century and for a large part of the 20th century is, according to Foucault, the discovery of the unconscious, we formulate the hypothesis that, between the 20th and 21st centuries, episteme has reconfigured itself around the paradigm of the mind as it has been redefined by the cognitive sciences, generating a new conception of man and of knowledge. Literature and the literary character represent the revelator of the new episteme but, in some cases, in accordance with the Foucauldian conception of literature, they can also constitute a space that escapes it, that resists it.